Interpolation of monogenic functions by using reproducing kernel Hilbert spaces - Cerejeiras, Paula (2018)
In this paper, we present results on interpolation of monogenic functions in the unit ball of R^3 using reproducing kernels and randomly chosen interpolation points. The main theoretical results are proved based on the concept of uniformly discrete sequences. Furthermore, estimates for the interpolation error as well as for the eigenvalues of the interpolation problems are presented. Numerical results are presented in the end.